Tangramrine: A novel graphical recognition and cued-recall based password system - Altamirano, Steven (2015)
Graphical passwords are an authentication user model that consists of the recall of pictures or graphics signs to gain access to a system. They have been proved to be a secure and reliable alternative to textual passwords; by giving a more robust schema against brute force and shoulder-surfing attacks. In this research paper we present an alternative to a graphical password based on a modification of the Tangram game. We believe our proposal accomplishes the features of being an easy recognition-based system password giving the user enough security against common threats such as brute force attacks by dictionary means or OCR types, as well as shoulder-surfing attacks.